1997
DOI: 10.1097/00005537-199710000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Survival, Function, and Quality of Life After Total Glossectomy

Abstract: Advanced tongue cancer is associated with poor survival despite aggressive therapy. In an attempt at cure, many patients undergo total glossectomy, which significantly affects function and quality of life (QOL). This study was designed to determine the survival rate and QOL of patients who had undergone total glossectomy. A total of 54 patients underwent total glossectomy, with or without total laryngectomy, for advanced tongue cancer from 1970 to 1996. Patient outcomes were assessed for the following: 1. dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 15 publications
(43 reference statements)
4
65
3
Order By: Relevance
“…As an example, despite sorne cancer patients reporting significant functional impairment, surprisingly high levels of quality of life has been observed (Ruhl et al, 1997). A cohort study with 153 head ~nd neck patients found that high levels of depressive symptons, low performance status, and combined modality treatment were significant predictors of poor functioning and psychological morbidity after treatment (De Graeff et al, 2000b).…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…As an example, despite sorne cancer patients reporting significant functional impairment, surprisingly high levels of quality of life has been observed (Ruhl et al, 1997). A cohort study with 153 head ~nd neck patients found that high levels of depressive symptons, low performance status, and combined modality treatment were significant predictors of poor functioning and psychological morbidity after treatment (De Graeff et al, 2000b).…”
Section: Quality Of Lifementioning
confidence: 99%
“…Furtherrnore, Allison et al (1999) suggested that the dental status may play an important role in the quality of life of head and neck cancer patients (Alli son et al, 1999). Finally, support from the farnily, friends (Ruhl et al, 1997) and the farnily doctor (Mathieson et al, 1996), and the patients' perception of the disease (i.e. state of rnind and optrnism) (Allison et al, 2000;Allison et al, 2003;Greer et al, 1992) may favorably influence the disease recovery and be of great value for the patients' quality of life.…”
Section: Quality Of Lifementioning
confidence: 99%
“…This average implies that only 20% of total glossectomy patients survive for a period of five years. Ruhl et al (1997Ruhl et al ( :1321 reported survival of 51% and 41% at three and five years respectively for 54 total glossectomy patients.…”
Section: Survival Ratesmentioning
confidence: 99%
“…Surgical resection, followed by immediate reconstruction, neck dissection (unilateral/bilateral) and post-operative radiation therapy is considered the favoured combination of treatment modalities for patients with advanced tongue disease (Salibian, Allison, Rappaport, Krugman, McMicken & Etchepare, 1989:513;Sultan & Coleman, 1989:298;Shah, 1996:175;Mactay, Perch, Markiewicz, Thaler, Challian, Goldberg, Kligerman & Weinstein, 1997:495;Ruhl, Gleich & Gluckman, 1997:1316Robertson, Gleich, Barrett & Gluckman, 2001:1364.…”
Section: Oncological and Surgical Management Of Advanced Tongue Cancermentioning
confidence: 99%
See 1 more Smart Citation